The Formal Validity of Children's Status Reviewed in Terms of Maslahah Mursalah - Nabila Inita Zahra; Endri Yenti (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Children born from sirri marriages still have the right to receive state administrative services and be recognized as citizens without requiring verification of their parents' marital status, as stipulated in Article 4 paragraph (2) of the Ministry of Home Affairs Regulation Number 9 of 2016. Therefore, it is important to assess the validity of Article 4 paragraph (2) through the perspective of maslahah mursalah. This study aims to analyze the validity of this provision in light of the principles of maslahah mursalah in Islamic law, using a field study approach. The research was conducted in a specific region, involving key informants, including state administrative officials, couples in sirri marriages, and religious leaders. Data collection methods included in-depth interviews, observation, and documentation. The results show that the implementation of Article 4 paragraph (2) provides a real solution for couples unable to fulfill the requirements for isbat nikah. This policy not only facilitates administrative services for children born from sirri marriages but also aligns with Islamic law's goal of achieving maslahah, particularly in protecting the rights of children. This research contributes significantly by examining the legal validity of sirri marriages from the perspective of maslahah mursalah and offering recommendations for regulatory reform to accommodate the rights of children born from sirri marriages in a fair and just manner according to Islamic legal principles.